Inside an elusive mind, Prabhakaran : the first profile of the world's most ruthless guerrilla leader - Narayan Swamy, M. R. (Delhi : Konark Publishers, 2003)
Biography of Velupillai Prabhakaran, b. 1954, Tamil political extremist and guerrilla leader and head of Liberation Tigers of Tamil Ealam, subversive group from Sri Lanka
Includes index
Keywords: Prabhakaran, Velupillai, -- 1954-; Radicals -- Sri Lanka -- Biography; Guerrillas -- Sri Lanka -- Biography; Tamil (Indic people) -- Sri Lanka -- Biography; Sri Lanka -- Politics and government, -- 1978-